Perfecting the Cluster Development in the Regional Dairy Products Subcomplex of the Russian Agro-Industrial Complex - ZAVOROTIN, E. F.; YURKOVA, M. S.; SERDOBINTSEV, D. V.; LIKHOVTSOVA, E. A.; VOLOSHCHUK, L. A. (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018, 2018)
A considerable increase in prices for raw milk in Russia in 2013-2015 and the support for beginner farmers had an impact on improving the intensity of production in the dairy cattle breeding. However, due to the high share of the population’s households in the structure of milk production (about 45%) and its low marketability (about 34%), there is a deficit and dependence on import. At the same time, the tempos of the growth of prices for raw milk cannot provide producers with development due to the delay of cost increase, reduction of the consumer demand and high price competition with exporters from Belarus. All this is a consequence of the lack of an efficient system of re-allocating the created value between sectors of the dairy products subcomplex of the agro-industrial complex of the Russian Federation, the servicing area, and trade. The creation of agro-industrial clusters in regions will solve such problems as the non-participation of the state in regulating the price formation on the milk and dairy products market, the lack of a transparent mechanism to stipulate the retail price for dairy products, infrastructure problems, innovative and investment development, etc. The research allowed us to substantiate the possibility of creating a dairy products cluster in the Saratov Region. Forming a logistic model and comparing algorithms of commodity circulation, it was determined that functioning of the cluster would exclude duplication of production and marketing functions and reduce the total costs by more than 40% on average. Prerequisites will be made to increase production volumes, to develop the infrastructure of the region and rural areas, and to increase the population’s employment, which will make up a huge social and economic effect at the minimal cost.